What is a price? basics of economic literacy - Learning seed ([Lake Zurich, IL] : Learning Seed, 2006)
Viewers will learn how prices are assigned to objects, who benefits from them, and how prices can influence a shopper's choice of purchase
Title from title screen
Producers: Jeffrey Schrank, Joseph Lombardo ; writer: Jeffrey Schrank
Narrator: Todd Neumann
Keywords: Pricing; Economics -- Study and teaching; Marketing -- Management